Diagnóstico e plano de melhoria da gestão dos resíduos sólidos (classe II) em uma universidade federal - Rossi, Salete de (2017)
Among the types of waste, Class II solid waste deserves to be highlighted, since they represent a substantial portion of all waste generated and, when poorly managed, become a sanitary, environmental and social problem. In the last two decades, a growing number of higher education institutions have been working to incorporate and institutionalize sustainability into their systems. The purpose of this study was to propose an improvement plan for the Solid Waste Management Class II of the Federal University of Espírito Santo, Campus Goiabeiras. Questionnaires and interviews were used to collect information from managers, administrative technicians, teachers and cleaning staff regarding the management of solid waste on campus, which allowed conclusions and recommendations on the changes needed to make solid waste management in the organization more efficient . The great challenge was to gather experiences, analyze, discuss and design a proposal that is realistic enough that the agents of this institution identify with the context and feel motivated to walk towards a transformation. The research results indicated that managers, administrative technicians and teachers are receptive to the implementation of Selective Collection and other actions to improve the treatment of waste in general. Although they do not have a formal instruction to correct segregation of solid waste, some sectors already carry out this separation on their own initiative. This pre-provision can contribute to the implementation of the proposals presented in this paper.